Project Manager and Stress in Coping with Demanding Situations in Automotive Industry - Róbert Modranský; Kateřina Bočková; Michal Hanák (Ital Publication, 2020)
Coping with demanding situations is a part of managerial work at different levels and in different contexts. In the presented paper, based on the theoretical and methodological analysis of knowledge in the field of coping and special coping with demanding situations in project manager work, we present the results and knowledge related to the possibility of researching and identifying procedures for coping with demanding situations in project management. Attention is focused on the identification of ways of coping with demanding situations in project manager work through the BSMW Questionnaire - Behaviour Strategies in Managerial Work as a tool for identifying these procedures. We present findings related to the analysis of the assessment of strategies for managing demanding situations in project manager work in Slovak automotive industry in the context of selected personality, socio-demographic characteristics of managers and situational conditions. The acquired results verified the meaningfulness of the empirical-inductive principle of detecting the ways of coping with the examined demanding situations and determining the taxonomy of these principles with the specification of five factors – emotional factor of coping, cognitive factor of coping I, cognitive factor of coping II, behavioural factor of coping I and behavioural factor of coping II. From the methodological viewpoint our results contribute to the discussion about the interactional approach in research in social sciences and about the question of dispositional or situational conception of methods of researching in this area of knowledge. Doi: 10.28991/esj-2020-01241 Full Text: PDF